The anti‐inflammatory drug celecoxib inhibits t‐type Ca2+ currents in spermatogenic cells yet it elicits the acrosome reaction in mature sperm. Issue 15 (13th June 2013) - Balderas, E.; Sánchez-Cárdenas, C.; Chávez, J.C.; de la Vega Beltrán, J.L.; Gómez-Lagunas, F.; Treviño, C.L.; Darszon, A.
Abstract : Celecoxib (Cx), an anti‐inflammatory drug designed to inhibit COX2, can affect some ion channels. T‐type (CaV 3) channels have been implicated in sperm physiology. Here we report and characterize the Cx induced inhibition of T‐type channels in mouse spermatogenic cells. Unexpectedly, Cx can also induce the acrosome reaction (AR), an intracellular Ca 2+ ([Ca 2+ ]i ) increase and a sperm depolarization. This [Ca 2+ ]i increase possibly results from the ability Cx has to alkalinize intracellular pH (pHi ), which is known to activate the sperm specific Ca 2+ channel CatSper. As the Cx induced [Ca 2+ ]i increase is sensitive to mibefradil, a CatSper blocker, this channel may mediate the Cx‐induced Ca 2+ entry leading to the AR. Our observations demonstrate that Cx can compromise fertilization. Abstract : Celecoxib inhibits T‐type Ca 2+ channels in spermatocytes at micromolar concentrations. The acrosome reaction induced by celecoxib points to the involvement of a Ca 2+ conductance in addition to CaV s. Celecoxib induces a Ca 2+ rise sensitive to mibrefadil suggesting CatSper participation. Alkalinization caused by celecoxib suggests an indirect effect on CatSper and Slo3. Broadly commercialized, commonly used celecoxib may hinder critical steps of fertilization.